Bayesian regression of piecewise homogeneous Poisson processes - Diego Sevilla (Papers in Physics, 2015)
In this paper, a Bayesian method for piecewise regression is adapted to handle counting processes data distributed as Poisson. A numerical code in Mathematica is developed and tested analyzing simulated data. The resulting method is valuable for detecting breaking points in the count rate of time series for Poisson processes.